2014
DOI: 10.1021/am5032874
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Polymer-Mediated Formation of Laponite-Based Nanohybrids with Robust Stability and pH Sensitivity for Anticancer Drug Delivery

Abstract: The development of pH-sensitive drug delivery nanosystems that present a low drug release at the physiological pH and are able to increase the extent of the release at a lower pH value (like those existent in the interstitial space of solid tumors (pH 6.5) and in the intracellular endolysosomal compartments (pH 5.0)) is very important for an efficient and safe cancer therapy. Laponite (LP) is a synthetic silicate nanoparticle with a nanodisk structure (25 nm in diameter and 0.92 nm in thickness) and negative-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 56 publications
1
74
0
Order By: Relevance
“…One biomedical application to which silicate clays are uniquely suited is hemostasis. Kaolinite has been used to evaluate blood‐clotting disorders since the 1950s, and a zeolite product (QuikClot) is approved for controlling hemorrhages . Recently, silicate clay nanomaterials have been investigated for improving hemostatics .…”
Section: Silicate Clays As Bioactive Nanomaterials For Biomedical Appmentioning
confidence: 99%
“…One biomedical application to which silicate clays are uniquely suited is hemostasis. Kaolinite has been used to evaluate blood‐clotting disorders since the 1950s, and a zeolite product (QuikClot) is approved for controlling hemorrhages . Recently, silicate clay nanomaterials have been investigated for improving hemostatics .…”
Section: Silicate Clays As Bioactive Nanomaterials For Biomedical Appmentioning
confidence: 99%
“…The system showed pH sensitivity and a sustained in vitro release . Using a different approach, Wang et al proposed the design of a nanocomposite formulation based on laponite hybridized with a polyethylene glycol and polylactic acid copolymer (PEG–PLA) as pH‐sensitive carriers of DOX . In this case, a self‐assembling process of the amphiphilic PEG–PLA copolymer on the surface of the laponite was achieved.…”
Section: Nanohybrids For Drug Deliverymentioning
confidence: 99%
“…It has pH‐dependent edge surface charges and a large specific surface area as high as 370 m 2 /g, which offer a high loading capacity and pH‐controllable release for a Lap‐based drug delivery system. One research group concentrated on the preparation and application of the Lap‐based drug delivery system in cancer therapy. They found that Lap showed high biocompatibility and enhanced encapsulation efficiency for drugs.…”
Section: Introductionmentioning
confidence: 99%
“…The loading of the drugs is mainly through the electrostatic interaction between negatively charged polyelectrolytes and the positively charged Lap . To reach a high loading capacity, the pH of the system should be kept above 9.0 to guarantee the negative charges of Lap are big enough . In this work, the fabrication was done at pH 3.2 by alternately depositing water‐soluble weak positive polyelectrolyte polyurethane (PU) and poly(acrylic acid) (PAA)‐Lap nanocomposites on a glass slide.…”
Section: Introductionmentioning
confidence: 99%